Surgical treatment of postoperative sternal mediastinitis using titanium nickelide implant - M. V. Shvedova; G. T. Dambaev; A. N. Vusik (Acta Biomedica Scientifica)
Postoperative sternal dehiscence is a severe complication of cardiac surgery. The aim of the study was to evaluate the outcomes of different surgical treatment tactics in patients with postoperative sternal mediastinitis. A total of 41 patients with postoperative sternal mediastinitis were studied from 2010 to 2014. Patients comprised 29 men (70,7%) and 12 women (29,3%) aged 61,12 ± 8,62 years. The first stage of surgical intervention included: secondary surgical debridement; surgical debridement with metal osteosynthesis (MOS) by metal suture (configurations: 1-1-1-1-1-1; 1-Х-1-1-1-1; 1-8-8-8) and longitudinal MOS of the left middle third of the sternum + transverse MOS (configurations: Z-Z-Z and 1-1-88-1-1 among others); sternal resynthesis with mesh titanium nickelide implant according to originally designed method (patent of the Russian Federation N 2489097). The study demonstrated that routine sternoraphy is not recommended in patients who underwent operations involving median sternotomy or if the re-thoracotomy is required due to infection complication in the sternum and anterior mediastinum. Indeed, this method did not result in recovery in 72,22% of cases and even worsened sternal fragmentation. In case of the absence of severe sternal fragmentation and when elimination of acute inflammation was achieved (surgical debridement, correct antibiotic therapy, and bandaging), sternal resynthesis with mesh titanium nickelide implant was preferable. Combination of this method with surgical debridement of the sternum and anterior mediastinum was acceptable in patients with chronic sternal osteomyelitis and mediastinitis. The method of sternal resynthesis with mesh titanium nickelide implant achieved good immediate results and secure fixation of the sternal fragments with recovery of sternal continuity. This method should be indicatedfor treatment of patients without severe sternal fragmentation.